Vinyl alcohol polymer
A vinyl alcohol-based polymer with controlled transmittance and yellow index is developed to address fluid loss issues in oil-well cement, enhancing performance under severe conditions while maintaining slurry fluidity and reducing costs.
Patent Information
- Application Number
- JP2022540171
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-31
- Filing Date
- 2021-07-15
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2041-07-15
AI Technical Summary
Existing polyvinyl alcohol-based polymers used as fluid loss reducing agents in oil-well cement fail to provide sufficient performance under high temperature and pressure conditions, leading to thickening of the cement slurry and increased costs due to the need for higher agent amounts.
A vinyl alcohol-based polymer with specific transmittance and yellow index characteristics, obtained by saponifying a homopolymer or copolymer of vinyl ester and polyfunctional monomers, is developed to enhance fluid loss reduction without excessive crosslinking, using controlled copolymerization and saponification processes.
The polymer effectively reduces fluid loss in oil-well cement under high temperature and pressure conditions, maintaining slurry fluidity and reducing costs by optimizing transmittance and yellow index values.
Smart Images

Figure 0007629018000002 
Figure 0007629018000003 
Figure 0007629018000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a vinyl alcohol polymer useful as an additive for oil well cement. [Background technology]
[0002] Oil well cement is used in cementing oil wells, gas wells, steam wells for geothermal power generation, etc. It is filled into the gap between the steel pipe (casing) and the well to protect the steel pipe. When the water content of the cement slurry is lost (fluid loss) due to the high pressure during injection and the heat from the earth, the fluidity and strength after hardening are impaired, so a fluid loss reducing agent is added.
[0003] One example of a fluid loss reducing agent is polyvinyl alcohol (hereinafter referred to as PVA). In recent years, as shale gas wells have been mined deeper, the pressure and temperature conditions have become more severe, and the amount of fluid loss reducing agent added has increased. However, increasing the amount of fluid loss reducing agent added increases the viscosity of the cement slurry, reducing its fluidity and increasing costs, so there is a demand for improving the fluid loss reducing performance of the agent itself.
[0004] Patent documents 1 and 2 describe the use of PVA as a fluid loss reducing agent, but the fluid loss reducing performance required for cement slurries injected under high temperature and pressure is insufficient. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2007 / 146348 [Patent Document 2] JP 2015-196733 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a vinyl alcohol polymer which is useful as an additive for oil well cement. [Means for solving the problem]
[0007] That is, the present invention relates to a vinyl alcohol polymer obtained by saponifying a homopolymer of a vinyl ester monomer or a copolymer of a vinyl ester monomer and a polyfunctional monomer, and having a difference (AB) of 5 to 25 between the transmittance (A) of a 1% by mass aqueous solution at 660 nm and the transmittance (B) of a 1% by mass aqueous solution at 430 nm. The vinyl alcohol polymer preferably has a transmittance of 95% or less in the entire wavelength region of 200 nm to 800 nm in a 1% by mass aqueous solution, and a yellow index of 10 or less. Vinyl alcohol polymers are useful as additives for oil well cements. Effect of the Invention
[0008] According to the present invention, there is provided a vinyl alcohol polymer which is useful as an additive for oil well cement. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a diagram showing the transmittance of a vinyl alcohol polymer according to an example at wavelengths of 200 nm to 1000 nm. [Diagram 2] FIG. 2 is a diagram showing the transmittance of a vinyl alcohol polymer according to a comparative example at wavelengths of 200 nm to 1000 nm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the preferred embodiments. However, the present invention is not limited to the preferred embodiments described below.
[0011] The vinyl alcohol polymer of the present invention is obtained by saponifying a homopolymer of a vinyl ester monomer or a copolymer of a vinyl ester monomer and a polyfunctional monomer, and has a difference (AB) of 5 to 25 between the transmittance (A) of a 1% by mass aqueous solution at 660 nm and the transmittance (B) of a 1% by mass aqueous solution at 430 nm.
[0012] Examples of the vinyl ester monomer include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, etc., and mixtures of these may also be used. From the viewpoint of ease of polymerization, it is preferable to use vinyl acetate.
[0013] As the polyfunctional monomer to be copolymerized with the vinyl ester monomer, a compound having two or more polymerizable unsaturated bonds in the molecule can be used, and examples thereof include divinyl ethers such as ethanediol divinyl ether, propanediol divinyl ether, butanediol divinyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, and polypropylene glycol divinyl ether, and divinyl sulfonic acid compounds.
[0014] Also, diene compounds such as pentadiene, hexadiene, heptadiene, octadiene, nonadiene, and decadiene, and diallyl ether compounds such as glycerin diallyl ether, diethylene glycol diallyl ether, ethylene glycol diallyl ether, triethylene glycol diallyl ether, polyethylene glycol diallyl ether, trimethylolpropane diallyl ether, and pentaerythritol diallyl ether. Triallyl ether compounds such as glycerin triallyl ether, trimethylolpropane triallyl ether, and pentaerythritol triallyl ether. Tetraallyl ether compounds such as pentaerythritol tetraallyl ether. Monomers containing an allyl ester group such as diallyl phthalate, diallyl maleate, diallyl itaconate, diallyl terephthalate, and diallyl adipate. Diallylamine compounds such as diallylamine and diallylmethylamine, and monomers containing an allylamino group such as triallylamine. Monomers containing an allylammonium group such as diallylammonium salts such as diallyldimethylammonium chloride. Additionally, there are monomers containing two or more allyl groups, such as triallyl isocyanurate, 1,3-diallyl urea, triallyl phosphate, and diallyl disulfide.
[0015] Further, monomers having (meth)acrylic acid such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, glycerin di(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and isocyanuric acid tri(meth)acrylate. Also included are monomers having (meth)acrylamides such as N,N'-methylenebis(meth)acrylamide and N,N'-ethylenebis(meth)acrylamide, divinylbenzene, and trivinylbenzene.
[0016] Among these compounds, from the viewpoints of reactivity with vinyl ester monomers, resistance to decomposition in the saponification reaction, and the like, compounds having a carbonyl group or an amide group in the molecule are preferred, and in particular, triallyl isocyanurate is preferably used.
[0017] When a polyfunctional monomer is copolymerized, the copolymerization amount of the structural units derived from the polyfunctional monomer is preferably 0.001 to 1.0 mol %, more preferably 0.005 to 0.5 mol %, and even more preferably 0.01 to 0.2 mol %, relative to 100 mol % of the structural units derived from the vinyl alcohol units in the vinyl alcohol-based polymer. By adjusting the copolymerization amount of the polyfunctional monomer within these ranges, the effect of reducing fluid loss can be sufficiently obtained, and the obtained vinyl alcohol polymer is not excessively crosslinked, so that the workability is not deteriorated.
[0018] The copolymerization amount of the polyfunctional monomer can be calculated by the following procedure using a total nitrogen trace analyzer TN-2100H (Nitto Seiko Analytech Co., Ltd.). A sample of vinyl alcohol polymer is collected on a quartz board, which is set in an auto boat controller ABC-210 (Nitto Seiko Analytech Co., Ltd.) and automatically inserted into an electric furnace, where it is burned in an argon / oxygen stream. The NO gas generated during this process is measured with a chemiluminescence detector. A calibration curve is created in advance using a standard solution (N-pyridine / toluene), and the nitrogen concentration is calculated from the calibration curve. Measurement conditions Reaction tube: Double tube for ABC Electric furnace temperature Inlet Temp: 800℃, Outlet Temp: 900℃ Gas flow rate: Ar: 300 mL / min, O 2 : 300mL / min, Ozone: 300mL / min Sample size: approx. 9-15mg
[0019] The polymerization method of the vinyl ester monomer and the vinyl ester monomer and the polyfunctional monomer is not particularly limited, and known polymerization methods such as solution polymerization, suspension polymerization, bulk polymerization, etc. From the viewpoint of ease of operation and the ability to use a solvent common to the saponification reaction which is the next step, it is preferable to use a solution polymerization method in an alcohol, and it is particularly preferable to use methanol as the alcohol.
[0020] The vinyl alcohol polymer of the present invention is obtained by saponifying the homopolymer of the vinyl ester monomer obtained by the above-mentioned method or the copolymer of the vinyl ester monomer and a polyfunctional monomer.
[0021] The saponification reaction is carried out by dissolving a homopolymer of a vinyl ester monomer or a copolymer of a vinyl ester monomer and a polyfunctional monomer in an alcohol and adding an alkali catalyst or an acid catalyst. Examples of the alcohol include methanol, ethanol, butanol, etc. The use of methanol is particularly preferred because it is a common solvent in the polymerization method. The concentration of the homopolymer of the vinyl ester monomer or the copolymer of the vinyl ester monomer and the polyfunctional monomer in the alcohol is preferably 5 to 80% in terms of solid content concentration. As the alkali catalyst, an alkali metal hydroxide such as sodium hydroxide, potassium hydroxide, sodium methylate, sodium ethylate, potassium methylate, or an alkali catalyst such as an alcoholate can be used, and as the acid catalyst, an inorganic acid aqueous solution such as hydrochloric acid or sulfuric acid, or an organic acid such as p-toluenesulfonic acid can be used. The amount of these catalysts used is preferably 0.1 to 100 millimolar equivalents relative to the vinyl ester monomer unit. The reaction temperature during saponification is preferably in the range of 10 to 70°C, more preferably 30 to 50°C. The reaction time is preferably 1 to 10 hours.
[0022] The saponification degree of the vinyl alcohol polymer is preferably 70 to 99 mol %. By adjusting the saponification degree within this range, a sufficient fluid loss reduction effect can be obtained. From the viewpoint of the effect of reducing fluid loss, the degree of saponification is more preferably 75 to 98 mol %. In this specification, the "saponification degree" refers to a value calculated by measurement in accordance with JIS K6726 "3.5 saponification degree".
[0023] The difference (AB) between the transmittance (A) of a 1% by mass aqueous solution of the vinyl alcohol polymer of the present invention at 660 nm and the transmittance (B) of a 1% by mass aqueous solution at 430 nm is 5-25. The decrease in transmittance is mainly due to light absorption and scattering. The transmittance at 660 nm is generally an index of turbidity, and when light is irradiated to a turbid liquid, the light is scattered by the turbid particles and the transmitted light is reduced. In other words, the transmittance value at 660 nm depends on the amount of water-insoluble crosslinked vinyl alcohol polymer particles present, and the more the amount of particles present, the more scattering occurs, so the transmittance value decreases. On the other hand, the transmittance value at 430 nm depends on scattering and absorption. In the present invention, it was found that the presence of water-insoluble crosslinked PVA particles that scatter at these wavelengths is important for the fluid loss reduction effect. In the case of a general linear PVA that is uniformly dissolved in water, there is almost no scattering in a 1% aqueous solution, so the transmittance difference (AB) is less than 5. On the other hand, if the transmittance difference (AB) exceeds 25, a gel that causes adhesion is formed, making production extremely difficult.
[0024] The transmittance of a 1% by mass aqueous solution of the vinyl alcohol polymer of the present invention over the entire wavelength region of 200 nm to 800 nm is preferably 95% or less, more preferably 93% or less, and even more preferably 90% or less. The transmittance value in the entire wavelength range of 200nm to 800nm depends on the scattering of the vinyl alcohol polymer in water, and indicates the presence of fine particles of crosslinked vinyl alcohol polymer that scatters in the entire wavelength range. The vinyl alcohol polymer that scatters in the entire wavelength range reduces fluid loss, and by adjusting the transmittance to the above range, the effect of reducing fluid loss is improved. The transmittance in the entire wavelength range of 200nm to 800nm can be adjusted by appropriately adjusting the amount of copolymerization with the polyfunctional comonomer and the conversion rate of the monomer.
[0025] The transmittance of the vinyl alcohol polymer can be measured by the following procedure. An aqueous solution of a vinyl alcohol polymer adjusted to 1% by mass is used in a 20 mm quartz cell, and the transmittance (% T) in the range of 200 to 1000 nm is measured using a UV meter (UV-1800, Shimadzu Corporation).
[0026] The yellow index of the vinyl alcohol polymer of the present invention is preferably 10 or less, and more preferably 8 or less. The yellow index is an index that indicates the yellowness of vinyl alcohol polymers. Vinyl alcohol polymers with a high yellow index contain low molecular weight vinyl alcohol polymers. From the viewpoint of reducing fluid loss, the presence of low molecular weight vinyl alcohol polymers is undesirable, so it is preferable to adjust the yellow index to this range. The value of the yellow index can be adjusted by the degree of saponification, the amount of copolymerization of polyfunctional monomers, the amount of solvent during polymerization, etc.
[0027] The yellow index can be measured by the following procedure. The vinyl alcohol polymer is powdered and the XYZ display system value is obtained using a colorimeter (ZE 2000, Nippon Denshoku Industries Co., Ltd.). The YI value can be calculated from JIS K7373:2006 Plastics - Determination of yellowness and yellowing index 6. Calculation method (using auxiliary illuminant C).
[0028] The vinyl alcohol polymer of the present invention may be copolymerized with other monomers copolymerizable with the vinyl ester monomer and the polyfunctional monomer within the range not impairing the effects of the present invention. Examples of these other monomers include α-olefin monomers such as ethylene and propylene, (meth)acrylic acid alkyl ester monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, unsaturated amide monomers such as (meth)acrylamide and N-methylolacrylamide, unsaturated carboxylic acid monomers such as (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, and fumaric acid, and alkyl (methyl, ethyl, propyl) groups of unsaturated carboxylic acids. Examples of the monomer include ester monomers such as aryl ester monomers, anhydrides of unsaturated carboxylic acids such as maleic anhydride, salts of unsaturated carboxylic acids with sodium, potassium, ammonium, etc., glycidyl group-containing monomers such as allyl glycidyl ether and glycidyl (meth)acrylate, sulfonic acid group-containing monomers such as 2-acrylamide-2-methylpropanesulfonic acid or salts thereof, phosphoric acid group-containing monomers such as acid phosphooxyethyl methacrylate and acid phosphooxypropyl methacrylate, and alkyl vinyl ether monomers.
[0029] The viscosity average degree of polymerization of the vinyl alcohol polymer is preferably 1000 to 10000, more preferably 1500 to 6000, and further preferably 2000 to 5000. By adjusting the viscosity average degree of polymerization within these ranges, a sufficient fluid loss reduction effect can be obtained, and the cement slurry does not become too viscous and the flowability does not decrease.
[0030] The "viscosity average degree of polymerization" is a value calculated from the intrinsic viscosity [η] (g / dL) measured at 30° C. using an Ostwald viscometer with ion-exchanged water as a solvent, according to the following formula (1). log(P)=1.613×log([η]×104 / 8.29)···(1) Here, P represents the viscosity average degree of polymerization.
[0031] The vinyl alcohol polymer of the present invention is suitably used as an additive for oil well cement. The method for adding the vinyl alcohol-based polymer to the cement slurry is not particularly limited, and conventional methods such as a method of mixing it in advance with the dry cement composition and a method of mixing it when preparing the cement slurry are used.
[0032] The addition amount of the vinyl alcohol-based polymer is 0.01 to 30% bwoc. It is preferably 0.05 to 10% bwoc, and more preferably 0.1 to 5% bwoc. The term "cement-based weight" (bwoc) refers to the weight of the additive in dry form added to the cement composition based only on the solid content of the cement.
Examples
[0033] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited thereto. Unless otherwise specified, "parts" and "%" mean "parts by mass" and "mass%".
[0034] <Adjustment of PVA>
[0035] Example 1 Into a polymerization kettle equipped with a reflux condenser, a dropping funnel, and a stirrer, 100 parts by mass of vinyl acetate, 0.16 parts by mass of triallyl isocyanurate, 67.0 parts by mass of methanol, and 0.005 parts by mass of Peroyl NPP (Nippon Yushi Co., Ltd.) were charged, and polymerization was carried out at a temperature below the boiling point for 5 hours while stirring under a nitrogen stream. Polymerization was stopped when the conversion rate of vinyl acetate reached 50%, and the unreacted vinyl acetate monomer was removed outside the polymerization system by a conventional method to obtain a methanol solution of vinyl acetate resin.
[0036] To the methanol solution of the vinyl acetate resin obtained above, a methanol solution of sodium hydroxide (0.01 mol in terms of sodium hydroxide relative to vinyl acetate) was added, and a saponification reaction was carried out at 45 ° C for 50 minutes. The obtained reaction solution was heated and dried to obtain PVA according to Example 1 with a saponification degree of 80 mol%. The "saponification degree" was measured and calculated according to JIS K6726 "3.5 Saponification degree".
[0037] The dried PVA was crushed in a crusher, then sieved using a sieve with 500 μm openings. The product that passed through the sieve was crushed again in the crusher and thoroughly mixed with the product that passed through the sieve. PVA with adjusted particle size was obtained, with 0.1% by mass of particle sizes of 500 μm or more and 12.4% by mass of particle sizes of 75 μm or less. In addition, the time required for the ratio of particles of 500 μm or more to become 30 mass% or less in the primary crushing, and the time required for the ratio of particles of 500 μm or more to become 5 mass% or less in the re-crushing of the sieved product were confirmed through preliminary tests, and the crushing was carried out for each time.
[0038] Example 2 PVA was obtained in the same manner as in Example 1, except that the methanol solution of the vinyl acetate resin obtained in Example 1 was used and the amount of the methanol solution of sodium hydroxide added was adjusted so that the saponification degree of the PVA was 88 mol%.
[0039] The particle size of the dried PVA was adjusted using a grinder in the same manner as in Example 1, so that 0.2% by mass had particle sizes of 500 μm or more and 10.5% by mass had particle sizes of 75 μm or less.
[0040] Example 3 A PVA was obtained in the same manner as in Example 1, except that the methanol solution of the vinyl acetate resin obtained in Example 1 was used and the saponification degree of the PVA was changed to 98 mol %.
[0041] The particle size of the dried PVA was adjusted using a pulverizer in the same manner as in Example 1 to obtain PVA with particle sizes adjusted to 0.1% by mass of particles not smaller than 500 μm and 13.8% by mass of particles not larger than 75 μm.
[0042] Example 4 In a polymerization vessel equipped with a reflux condenser, a dropping funnel, and a stirrer, 100 parts by mass of vinyl acetate, 0.33 parts by mass of triallyl isocyanurate, 150.0 parts by mass of methanol, and 0.013 parts by mass of Peroyl NPP (NOF Corporation) were charged, and polymerization was carried out for 5 hours at boiling point while stirring under a nitrogen stream. When the conversion rate of vinyl acetate reached 69%, the polymerization was stopped, and unreacted vinyl acetate monomer was removed from the polymerization system by a conventional method to obtain a methanol solution of vinyl acetate resin.
[0043] A methanol solution of sodium hydroxide (calculated as 0.01 moles of sodium hydroxide relative to vinyl acetate) was added to the methanol solution of the vinyl acetate resin obtained above, and a saponification reaction was carried out for 50 minutes at 45° C. The resulting reaction solution was dried by heating to obtain a PVA according to Example 4 having a saponification degree of 80 mol%.
[0044] The dried PVA was crushed in a grinder, then sieved using a sieve with 500 μm openings. The product that passed through the sieve was crushed again in the grinder and thoroughly mixed with the product that passed through the sieve. PVA with particle size adjusted to 0.1% by mass of 500 μm or more and 10.8% by mass of 75 μm or less was obtained.
[0045] Example 5 In a polymerization vessel equipped with a reflux condenser, a dropping funnel, and a stirrer, 100 parts by mass of vinyl acetate, 0.04 parts by mass of triallyl isocyanurate, 21.0 parts by mass of methanol, and 0.003 parts by mass of Peroyl NPP (NOF Corporation) were charged, and polymerization was carried out for 5 hours at boiling point while stirring under a nitrogen stream. When the conversion rate of vinyl acetate reached 50%, the polymerization was stopped, and unreacted vinyl acetate monomer was removed from the polymerization system by a conventional method to obtain a methanol solution of vinyl acetate resin.
[0046] A methanol solution of sodium hydroxide (calculated as 0.012 moles of sodium hydroxide relative to vinyl acetate) was added to the methanol solution of the vinyl acetate resin obtained above, and a saponification reaction was carried out for 50 minutes at 45° C. The resulting reaction solution was dried by heating to obtain a PVA according to Example 5 having a saponification degree of 80 mol%.
[0047] The particle size of the dried PVA was adjusted using a pulverizer in the same manner as in Example 1 to obtain PVA with particle sizes adjusted to 0.1% by mass of particles not smaller than 500 μm and 11.2% by mass of particles not larger than 75 μm.
[0048] Example 6 In a polymerization vessel equipped with a reflux condenser, a dropping funnel, and a stirrer, 100 parts by mass of vinyl acetate, 0.09 parts by mass of triallyl isocyanurate, 43.0 parts by mass of methanol, and 0.04 parts by mass of Peroyl NPP (NOF Corporation) were charged, and polymerization was carried out for 5 hours at boiling point while stirring under a nitrogen stream. When the conversion rate of vinyl acetate reached 55%, the polymerization was stopped, and unreacted vinyl acetate monomer was removed from the polymerization system by a conventional method to obtain a methanol solution of vinyl acetate resin.
[0049] A methanol solution of sodium hydroxide (calculated as 0.01 moles of sodium hydroxide relative to vinyl acetate) was added to the methanol solution of vinyl acetate obtained above, and a saponification reaction was carried out for 90 minutes at 45° C. The resulting reaction solution was dried by heating to obtain PVA according to Example 6 having a saponification degree of 81.0 mol%.
[0050] The particle size of the dried PVA was adjusted using a grinder in the same manner as in Example 1, so that 0.1% by mass had a particle size of 500 μm or more and 12.1% by mass had a particle size of 75 μm or less.
[0051] Comparative Example 1 In a polymerization vessel equipped with a reflux condenser, a dropping funnel, and a stirrer, 100 parts by mass of vinyl acetate, 22.0 parts by mass of methanol, and 0.0013 parts by mass of Peroyl NPP (NOF Corporation) were charged, and polymerization was carried out at boiling point for 7 hours while stirring under a nitrogen stream. When the conversion rate of vinyl acetate reached 69%, the polymerization was stopped, and unreacted vinyl acetate monomer was removed from the polymerization system by a conventional method to obtain a methanol solution of vinyl acetate resin.
[0052] A methanol solution of sodium hydroxide (calculated as 0.013 moles of sodium hydroxide relative to vinyl acetate) was added to the methanol solution of the vinyl acetate resin obtained above, and a saponification reaction was carried out for 50 minutes at 45° C. The resulting reaction solution was dried by heating to obtain a PVA according to Comparative Example 1 having a saponification degree of 99 mol%.
[0053] The particle size of the dried PVA was adjusted using a pulverizer in the same manner as in Example 1 to obtain PVA with particle sizes adjusted to 0.1% by mass of particles not smaller than 500 μm and 13.8% by mass of particles not larger than 75 μm.
[0054] Comparative Example 2 In a polymerization vessel equipped with a reflux condenser, a dropping funnel, and a stirrer, 100 parts by mass of vinyl acetate, 67.0 parts by mass of methanol, and 0.015 parts by mass of Peroyl NPP (NOF Corporation) were charged, and polymerization was carried out at boiling point for 10 hours while stirring under a nitrogen stream. When the conversion rate of vinyl acetate reached 90%, the polymerization was stopped, and unreacted vinyl acetate monomer was removed from the polymerization system by a conventional method to obtain a methanol solution of vinyl acetate resin.
[0055] A methanol solution of sodium hydroxide (calculated as 0.018 moles of sodium hydroxide relative to vinyl acetate) was added to the methanol solution of the vinyl acetate resin obtained above, and a saponification reaction was carried out for 90 minutes at 45° C. The resulting reaction solution was dried by heating to obtain a PVA according to Comparative Example 2 having a saponification degree of 98 mol%.
[0056] The particle size of the dried PVA was adjusted using a pulverizer in the same manner as in Example 1 to obtain PVA with particle sizes adjusted to 0.2% by mass of particles not smaller than 500 μm and 11.1% by mass of particles not larger than 75 μm.
[0057] Comparative Example 3 In a polymerization vessel equipped with a reflux condenser, a dropping funnel, and a stirrer, 100 parts by mass of vinyl acetate, 2.7 parts by mass of dimethyl maleic acid (DMM), 50.4 parts by mass of methanol, and 0.018 parts by mass of Peroyl NPP (NOF Corporation) were charged, and polymerization was carried out for 9 hours at boiling point while stirring under a nitrogen stream. When the conversion rate of vinyl acetate reached 92%, the polymerization was stopped, and unreacted vinyl acetate monomer was removed from the polymerization system by a conventional method to obtain a methanol solution of vinyl acetate resin.
[0058] A methanol solution of sodium hydroxide (calculated as 0.014 moles of sodium hydroxide relative to vinyl acetate) was added to the methanol solution of the vinyl acetate resin obtained above, and a saponification reaction was carried out for 50 minutes at 45° C. The resulting reaction solution was dried by heating to obtain a PVA according to Comparative Example 3 having a saponification degree of 72 mol%.
[0059] The dried PVA was adjusted in particle size by a pulverizer in the same manner as in Example 1, and PVA with the particle size adjusted to 0.1% by mass or more of 500 μm or more and 12.2% by mass or less of 75 μm or less was obtained.
[0060] Comparative Example 4 Into a polymerization kettle equipped with a reflux condenser, a dropping funnel, and a stirrer, 100 parts by mass of vinyl acetate, 0.16 parts by mass of triallyl cyanurate (TAC), 67.0 parts by mass of methanol, and 0.003 parts by mass of Peroyl NPP (Nippon Oil & Fats Co., Ltd.) were charged, and polymerization was carried out at a temperature below the boiling point for 5 hours while stirring under a nitrogen stream. Polymerization was stopped when the conversion rate of vinyl acetate reached 45%, and the unreacted vinyl acetate monomer was removed from the polymerization system by a conventional method to obtain a methanol solution of a vinyl acetate resin.
[0061] To the methanol solution of the vinyl acetate resin obtained above, a methanol solution of sodium hydroxide (0.01 mol in terms of sodium hydroxide with respect to vinyl acetate) was added, and a saponification reaction was carried out at 45 °C for 50 minutes. The obtained reaction solution was heated and dried to obtain PVA according to Comparative Example 4 with a saponification degree of 80 mol%.
[0062] The dried PVA was adjusted in particle size by a pulverizer in the same manner as in Example 1, and PVA with the particle size adjusted to 0.1% by mass or more of 500 μm or more and 12.7% by mass or less of 75 μm or less was obtained.
[0063] <4% Viscosity> Regarding the PVA according to Examples 1 to 6 and Comparative Examples 1 to 4 obtained above, the viscosity was measured according to JIS K6726. However, an aqueous solution adjusted to 4% by mass was used as the measurement sample.
[0064] <Copolymerization Amount of Polyfunctional Monomer in PVA> Regarding the PVA according to Examples 1 to 6 and Comparative Examples 1 to 4 obtained above, the copolymerization amount of the polyfunctional monomer was calculated by the following method. The copolymerization amount of the polyfunctional monomer was calculated by the following procedure using a trace total nitrogen analyzer TN-2100H (Nitto Seiko Analytic Co., Ltd.). A sample of vinyl alcohol polymer was collected on a quartz board, which was set in an auto boat controller ABC-210 (Nitto Seiko Analytech Co., Ltd.) and automatically inserted into an electric furnace, where it was burned in an argon / oxygen stream. The NO gas generated during this process was measured with a chemiluminescence detector. A calibration curve was created in advance using a standard solution (N-pyridine / toluene), and the nitrogen concentration was calculated from the calibration curve. Measurement conditions Reaction tube: Double tube for ABC Electric furnace temperature Inlet Temp: 800℃, Outlet Temp: 900℃ Gas flow rate: Ar: 300 mL / min, O 2 : 300mL / min, Ozone: 300mL / min Sample size: approx. 9-15mg
[0065] <Transmittance difference> For the PVAs obtained in Examples 1 to 6 and Comparative Examples 1 to 4, aqueous solutions adjusted to 1% by mass were placed in 20 mm quartz cells, and the transmittance (%T) in the range of 200 to 1000 nm was measured using a UV meter (UV-1800, Shimadzu Corporation). The transmittance (A) at 660 nm was divided by the transmittance (A) at 430 nm to obtain the transmittance difference.
[0066] <YI(イエローインデックス)> The YI (yellow index) was measured for the PVA obtained above according to Examples 1 to 6 and Comparative Examples 1 to 4. The yellow index was measured according to the following procedure. The vinyl alcohol polymer was used as a powder to obtain values in the XYZ display system using an apparatus (ZE 2000, Nippon Denshoku Industries Co., Ltd.). The YI value was calculated according to JIS K7373:2006 Plastics - Determination of yellowness and yellowing index, 6. Calculation method (using auxiliary illuminant C).
[0067] <Fluid loss measurement> The fluid loss reduction effect of PVA was measured according to the fluid loss evaluation method of the American Petroleum Institute (API) standard 10B-2 (April 2013). The specific measurement procedure is shown below. Class G oil well cement was blended with 0.4 bwoc of PVA and set retarder (CR-270, Flotek Industries) in the amounts shown in Table 1, and mixed with water according to the procedure described in API Standard 10B-2 (April 2013) to obtain a cement slurry with a water content of 30 mass%. The resulting cement slurry was placed in a fluid loss evaluation tester (Model 7120, Chandler Engineering) and tested at the temperature shown in Table 1 under a pressure of 1000 psi according to the procedure described in API Standard 10B-2 (April 2013), and the fluid loss amount was calculated.
[0068] The results obtained are shown in Table 1.
[0069] [Table 1]
[0070] From Table 1, it was found that the additive for oil well cement containing the PVA obtained by the present invention can significantly reduce the fluid loss of oil well cement even at high temperatures. Figures 1 and 2 are diagrams showing the transmittance of vinyl alcohol-based polymers at wavelengths of 200 nm to 1000 nm in Examples 1 to 6 and Comparative Examples 1 to 4, respectively. As can be seen from Figure 1, it was found that a vinyl alcohol-based polymer having a transmittance of 95% or less in the entire wavelength range of 200 nm to 800 nm in a 1 mass% aqueous solution can significantly reduce the fluid loss of oil well cement even at high temperatures. On the other hand, as can be seen from Figure 2, the effect was not obtained in the comparative examples.
Claims
1. The additive for oil well cement is a vinyl alcohol-based polymer obtained by saponifying a homopolymer of a vinyl ester monomer or a copolymer of a vinyl ester monomer and a polyfunctional monomer, and has a difference (A-B) between the transmittance (A) of a 1% by mass aqueous solution at 660 nm and the transmittance (B) of a 1% by mass aqueous solution at 430 nm of 15.7 to 25.
2. An additive for oil well cement as described in claim 1, wherein the transmittance of a 1 mass % aqueous solution of the vinyl alcohol polymer over the entire wavelength range of 200 nm to 800 nm is 95% or less.
3. An additive for oil well cement as described in claim 1 or 2, wherein the yellow index of the vinyl alcohol-based polymer is 10 or less.
Citation Information
Patent Citations
Hydrophilic nonionic rigid gel
JP1980104301A
Polyvinyl alcohol-made medical hydrogel and manufacture therefor
JP2000157625A
Additive for slurry, drilling mud, and cement slurry
JP2015196733A
Vinyl alcohol-based polymer, and cement slurry using the same
JP2020079197A
Fluid loss additive with improved rheological properties
WO2007146348A2